Modelo de Séries Temporais Autorregressivo Periódico - PAR - Cavalaro, Natália Leite (Universidade Federal de São Carlos, 2021)
This work presents the study of a type of time series model, called of periodic autoregressive model, which emerged from the researches of Thomas and Fiering (1962), according to Hipel and McLeod (1994). Its use is mainly in series temporals that present a periodic behavior in the mean, variance and function of autocorrelation. Application examples will also be displayed, in which the time series presents the ideal characteristics of using the PAR model, and how to do the procedure of choice, study, suitability and prediction of this type of model, in addition to being carried out a comparison with the seasonal time series model.
Periodic Autoregressive Time Series Model - PAR
Keywords: Modelo Autorregressivo Períodico; Previsão; Sazonalidade; Séries temporais; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::PROBABILIDADE E ESTATISTICA APLICADAS